Analysis of Linguistic Elements in the Textbook of Al-Arabiyyah Li An-Nasyi'in and Its Contribution to the Arabic Language Development Program - Nur Faiz Kholidiyah (Abjadia, 2021)
This study aims to determine the suitability of the contents in the Textbook of Al-Arabiyyah Li An-Nasyi'in  with language elements and their contribution to the Arabic Language Development Program of the State Islamic University of Maulana Malik Ibrahim Malang. This research uses qualitative and quantitative approaches. Based on the data analysis that has been carried out, the results of this study indicate that 1) The percentage of the suitability of the Fonology, Morfology, Vocabulary, Listening, Speaking, Reading and Kitabah in the Textbook of Al-Arabiyyah Li An-Nasyi'in respectively is 25%, 85%, 75%, 30%, 55%, 35%, and 60%; 2) the percentage of the contribution level of the language element is 65.6% with the criteria of sufficient contribution.